2009
DOI: 10.1016/j.amjcard.2008.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking and Cardiovascular Risk in a Population With High Mean Alcohol Consumption

Abstract: Moderate alcohol consumption has been associated with lower coronary artery disease (CAD) risk. However, data on the CAD risk associated with high alcohol consumption are conflicting. The aim of this study was to examine the impact of heavier drinking on 10-year CAD risk in a population with high mean alcohol consumption. In a population-based study of 5,769 adults (aged 35 to 75 years) without cardiovascular disease in Switzerland, 1-week alcohol consumption was categorized as 0, 1 to 6, 7 to 13, 14 to 20, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 29 publications
5
87
4
1
Order By: Relevance
“…For instance, participants engaging in physical activity had higher odds of presenting with MHO, indicating that physical activity exerts beneficial effects on cardiovascular risk factors even among obese participants, a finding already known (Messier et al, 2008). Conversely, and contrary to a previous study (Wildman et al, 2008), no relationship was found between alcohol consumption and MHO, possibly due to the fact that a high alcohol consumption was associated with increased blood pressure (Foerster et al, 2009). Also, no relationship between MHO and smoking status was found, with the exception of MHO among overweight þ obese subjects using the criteria of Wildman et al (2008).…”
Section: Discussioncontrasting
confidence: 55%
“…For instance, participants engaging in physical activity had higher odds of presenting with MHO, indicating that physical activity exerts beneficial effects on cardiovascular risk factors even among obese participants, a finding already known (Messier et al, 2008). Conversely, and contrary to a previous study (Wildman et al, 2008), no relationship was found between alcohol consumption and MHO, possibly due to the fact that a high alcohol consumption was associated with increased blood pressure (Foerster et al, 2009). Also, no relationship between MHO and smoking status was found, with the exception of MHO among overweight þ obese subjects using the criteria of Wildman et al (2008).…”
Section: Discussioncontrasting
confidence: 55%
“…442 In evaluating the relationship between alcohol consumption and triglycerides, some studies have shown no association, [443][444][445] whereas others found modestly lower triglyceride levels in women who consumed up to 0.6 oz daily. 446 At higher intakes, triglyceride levels increase, 447,448 and Rimm et al 449 estimated that ingestion of 1 oz/d would correspond to a 5% to 10% higher triglyceride concentration than found in nondrinkers.…”
Section: Alcoholmentioning
confidence: 99%
“…Given that smoking falls into the category of major risk factors, prevention of smoking is of great importance (10). Taking high amounts of alcohol increases blood pressure, increases the risk of stroke, increased incidence of cardiomyopathy and cardiac arrhythmias (11). It is a significant development of the country, because it affects the health promotion strategy, which consequently changes the behavior based on individual needs, whose positive direction is one of the important goals.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that subjects who consume alcohol in biggest percentage (73.4%) consumed the same day, while the smallest percentage (2.7%) comprise the same subjects who consumed annually. Moderate alcohol consumption is not harmful to the cardiovascular system, but because of adverse social and health effects of alcohol on the population can not make recommendations for the safe amount of alcohol use (11 Table 8. frequency of alcohol consumption they are modified by oxidation is retained in the wall of arteries causing atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%